Salivary gland lactate dehydrogenase: A novel diagnostic test for anticipation of neurodevelopmental outcome in perinatal asphyxia in developing countries - Prasad, Roshan; Taksande, Amar; Singh Lakra, Mahaveer; Wanjari, Mayur (Bangabandhu Sheikh Mujib Medical University Journal, 2024)
Not available